2022
DOI: 10.1051/0004-6361/202142825
|View full text |Cite
|
Sign up to set email alerts
|

Spinning nano-carbon grains: Viable origin for anomalous microwave emission

Abstract: Context. Excess microwave emission, commonly known as anomalous microwave emission (AME), is now routinely detected in the Milky Way. Although its link with the rotation of interstellar (carbonaceous) nano-grains seems to be relatively well established at cloud scales, large-scale observations show a lack of correlation between the different tracers of nano-carbons and AME, which has led the community to question the viability of this link. Aims. Using ancillary data and spinning dust models for nano-carbons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
(110 reference statements)
1
4
0
Order By: Relevance
“…They find that PAH mass is better correlated with AME emission than total dust mass, and argue in support of electric dipole emission as the source of AME. This is in agreement with Ysard et al (2022), who compare dust/PAH correlations derived emission models with all-sky models across the full sky to show that nano-silicates are disfavored compared to a PAHbased origin of AME. Several authors have recently argued that environmental variations, which influence the amount, type, and excitation of PAH species present in a region of space, are critical to take into account in testing the relationship between the presence of PAH emission.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…They find that PAH mass is better correlated with AME emission than total dust mass, and argue in support of electric dipole emission as the source of AME. This is in agreement with Ysard et al (2022), who compare dust/PAH correlations derived emission models with all-sky models across the full sky to show that nano-silicates are disfavored compared to a PAHbased origin of AME. Several authors have recently argued that environmental variations, which influence the amount, type, and excitation of PAH species present in a region of space, are critical to take into account in testing the relationship between the presence of PAH emission.…”
Section: Discussionsupporting
confidence: 89%
“…A potential explanation for this finding within the spinning dust paradigm is that the AME arises from spinning grains that are not PAHs. It has been shown that nano-silicate grains could exist in sufficient abundance to explain the AME Hensley & Draine 2017), although Ysard et al (2022) have recently argued that these grains cannot reproduce the AME spectral energy distribution in detail. Spinning grains with a magnetic dipole moment could also contribute to the observed AME, though they are unable to account for the entirety of the emission (Hoang & Lazarian 2016;Hensley & Draine 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…fitting, and that doing so can obscure true correlations. A correlation between MIR and microwave emission could also be obscured if MIR PAH emission and spinning dust emission have markedly different emissivities in different interstellar environments, even if both are produced by PAHs (Hensley et al 2022a;Ysard et al 2022).…”
Section: Emissionmentioning
confidence: 99%
“…Finally, the association between the AME and PAHs has been questioned on the basis of a lack of correlation between the AME and MIR PAH emission after removing their mutual correlation with the FIR dust continuum (Hensley et al 2016). In response, some authors have suggested that the AME could arise from spinning nanosilicates instead Hensley & Draine 2017a), though Ysard et al (2022) have recently argued that emission from nanosilicates cannot reproduce the observed AME SED shape in detail. Another possibility advanced by Bell et al (2019) is that comparing broadband MIR and microwave fluxes is not as reliable as inferring parameters like PAH mass from SED The contributions to the model from vibrational and by rotational emission are plotted with green and blue dashed lines, respectively.…”
Section: Emissionmentioning
confidence: 99%